Clinical features, course, and outcomes of a UK cohort of pediatric moyamoya. (27th February 2018) - Tho-Calvi, Sara C.; Thompson, Dominic; Saunders, Dawn; Agrawal, Shakti; Basu, Anna; Chitre, Manali; Chow, Gabriel; Gibbon, Frances; Hart, Anthony; Tallur, Krishnaraya Kamath; Kirkham, Fenella; Kneen, Rachel; et al.
Abstract : Objective: To describe characteristics and course of a large UK cohort of children with moyamoya from multiple centers and examine prognostic predictors. Methods: Retrospective review of case notes/radiology, with use of logistic regression to explore predictors of outcome. Results: Eighty-eight children (median presentation age 5.1 years) were included. Thirty-six presented with arterial ischemic stroke (AIS) and 29 with TIA. Eighty had bilateral and 8 unilateral carotid circulation disease; 29 patients had posterior circulation involvement. Acute infarction was present in 36/176 hemispheres and chronic infarction in 86/176 hemispheres at the index presentation. Sixty-two of 82 with symptomatic presentation had at least one clinical recurrence. Fifty-five patients were treated surgically, with 37 experiencing fewer recurrences after surgery. Outcome was categorized as good using the Recovery and Recurrence Questionnaire in 39/85 patients. On multivariable analysis, presentation with TIA (odds ratio [OR] 0.09, 95% confidence interval [CI] 0.02–0.35), headache (OR 0.10, 95% CI 0.02–0.58), or no symptoms (OR 0.08, 95% CI 0.01–0.68) was less likely to predict poor outcome than AIS presentation. Posterior circulation involvement predicted poor outcome (OR 4.22, 95% CI 1.23–15.53). Surgical revascularization was not a significant predictor of outcome. Conclusions: Moyamoya is associated with multiple recurrences, progressive arteriopathy, and poor outcome in half of patients, especially with AIS presentation and posterior circulation involvement. Recurrent AIS is rare after surgery. Surgery was not a determinant of overall outcome, likely reflecting surgical case selection and presentation clinical status.